The Contributions of Sufism in Promoting Religious Harmony in Bangladesh - Al Masud, Abdullah; Abdullah, Md. Faruk; Amin, Md. Ruhul (Jurnal Usuluddin, 2017)
Sufism in Bangladesh is directly connected to the faith, history and culture of Bangladeshi Muslims. Sufis contributed by reducing religious hatred, fanaticism and fundamentalism of any kind among the people of Bangladesh. It has social and economic impacts as well on the people. The paper investigates the influence of Sufism in promoting religious harmony in Bangladesh from 11th to 20th century. It also focuses on the evolution of Sufism in Bangladesh and the history of famous Sufis who were involved in establishing co-existence and peaceful societies there. This study is an attempt to find a way to unite all people of different religions and movements in the world.